SKRINING AKTIVITAS ENZIM Bacillus sp. YANG DIISOLASI DARI TAMAN NASIONAL GUNUNG HALIMUN - Iman Hidayat (Research Center for Biology-Indonesian Institute of Sciences, 2004)
Fifty strains of Bacillus sp. isolated from Gunung Halimun National Park (GHNP) were characterized. All strains are characterized by amylase, protease, phosphatase, ligninase, and cellulase activity.Thirtyseven isolates gave positive reaction for amylase activity, 46 isolates for protease activity, 3 isolates for phosphatase activity, 3 isolates for ligninase activity, and 36 isolates for cellulose activity.These findings indicates that Bacillus sp. that isolated from GHNP is a potential microbe for enzymes technology and biotechnology application.